Deletions in vaccine strains of pseudorabies virus and their effect on synthesis of glycoprotein gp63. - Petrovskis, E A (1986)
The pseudorabies virus vaccine strains Norden and Bartha each have been reported to have deletions in the small unique component of the genome (B. Lomniczi, M. L. Blankenship, and T. Ben-Porat, J. Virol. 49:970-979, 1984). The deletion in Norden was shown to delete the entire coding region for gI but not any of the coding sequences for gp63. However, gp63 in Norden-infected cells was only 36 kilodaltons, and a 44-kilodalton form of gp63 was released into the medium. In Bartha, the deletion removed the coding region for all but 89 amino acids of gp63, and no gp63 was detected in either Bartha-infected cells or medium.